The Debate about Argument and Spirit of Works of Al-Gazālī’s and Ibn Rushd’s as well as the Implication on Islamic Thoughts - Fathurrahman Muhtar (Universitas Islam Negeri Mataram, 2016)
The decline of Islamic science is seen as impacts of al-Gazālī’s criticism to philosophy and controversy surrounding the thought of al-Gazālī and Ibn Rushd. During the Golden Age in the medieval period, Muslim scholars and philosophers had been the world references for science and technology development. They lost this legacy because they embraced orthodoxy rather than rationality. Al-Gazālī had written a book called Tahāfut al-Falāsifah (The Collapse or Inconsistence of the Philosophers) which criticised Islamic philosophers especially Ibn Sīnā and Al-Fārābī. Later after the death of al-Gazālī, Ibn Rushd wrote book tahāfut al-tahāfut which commented on al-Gazālī’s book Tahāfut al-falāsifah. It was arguing over Muslims should advance in science and technology in this modern era as it was evident during the Golden Age Islamic Era (the 7th up to the 13th centuries) whereby Muslims were the world references in science and technology development. However, after the period Muslims abandoned rationality and have remained so up to the present. This situation caused Islamic thoughts to move from rationality to orthodoxy. Al-Gazālī has been considered as the cause of the decline in Islamic Thought as he critiqued Islamic philosophers especially Ibn Sīnā and al-Fārābī in his book Tahāfut al-Falāsifah. Later Ibn Rushd wrote book Tahāfut al-Tahāfut which commented on al-Gazālī’s book Tahāfut al-Falāsifah. DOI: http://dx.doi.org/10.20414/ujis.v20i1.804